Reliability analysis of complex water distribution systems: the role of the network connectivity and tanks. Issue 1 (20th December 2021) - Berardi, L.; Laucelli, D.; Ciliberti, F.; Bruaset, S.; Raspati, G.; Selseth, I.; Ugarelli, R.; Giustolisi, O.
Abstract: A reliable water distribution network (WDN) can provide an adequate supply service to customers under both normal and abnormal working conditions. The WDN reliability analysis, therefore, is a keystone to improve the supply service efficiency. Strategies for reliability analysis are usually proved on small WDNs, which do not compare with large real complex systems in terms of number of water tanks, pressure reduction valves, variable speed pumps, controlled devices and possible alternative water supply schemes. The topological changes due to pipeline interruptions impact on emptying–filling of water tanks and network pressure status. This work proposes a two-level procedure for mechanical reliability assessment, suited for large real WDNs. It leverages a path/connectivity-based approach to set up reliability indicators for global-level analysis and local screening of the most critical scenarios. The employed advanced hydraulic model includes the automatic detection of topological changes and the robust modelling of water level in tanks using the generalized global gradient algorithm. The extended period simulation enables the reliability assessment of alternative water supply schemes and the sensitivity of tanks and controlled devices to single failure events. The procedure is demonstrated on a real complex network, being consistent with the ongoing digital transition in the WDN management sector. HIGHLIGHTS: Demonstrating the key features of advanced hydraulic models to get effective reliability analysis in large WDNs with multiple tanks and controlled devices. Novel structured procedure to assess reliability in large complex WDNs based on global and local indicators accounting for unsupplied water to consumers and water deficit in tanks. Demonstration on a real WDN with unprecedented complexity in the literature.